Characterization of a novel calcium phosphate cement–calcium sulfate hemihydrate–acemannan for vital pulp therapy - Bryan Wangidjaja; Widyastuti, Wiena; Elline; Sudiono, Janti (Universitas Airlangga, 2025)
Background: Dental caries remains as one of the most prevalent oral diseases worldwide, especially in developing nations like Indonesia. Untreated caries may lead to pulp involvement, prompting vital pulp therapy (VPT) to protect pulp vitality. The success of VPT is dependent on the biological and physical properties of the capping materials. Traditional pulp capping materials, such calcium hydroxide Ca(OH)₂ and mineral trioxide aggregate (MTA), show bio-activity but are limited by issues of solubility, manipulation, and bio-compatibility. Consequently, calcium phosphate cement (CPC) and calcium sulfate hemihydrate (CSH) with acemannan (Ace) have been explored as potential alternatives. Purpose: This research aimed to evaluate the potential of a mixture containing CPC-CSH-Ace as a bio-active material for vital pulp therapy. Methods: CPC–CSH–Ace was formulated by combining 70 wt% CPC and 30 wt% CSH with acemannan concentrations of 3 wt%, 5 wt%, and 10 wt%. Calcium hydroxide (Dycal, Dentsply) and MTA (Bio MTA+, Cerkamed) were used as controls. Particle size was measured using a Particle Size Analyzer (Horiba SZ-100), surface morphology and calcium ratio were tested with SEM–EDS, and crystal structure was determined using XRD (Rigaku Miniflex). Data were examined utilizing one-way ANOVA and subsequent post-hoc testing (p < 0.05). Results: CPC–CSH–Ace exhibited smaller particle sizes, smoother surfaces, higher Ca/P ratios, and more defined hydroxyapatite peaks than Ca(OH)₂ and MTA. Conclusion The combination of CPC–CSH-Ace showed significant chemical and physical characteristics and has promise as a new bio-active material for vital pulp therapy.